LANGERHANS CELLS HISTIOCYTOSIS IN ONE FAMILY - Sh. Ansari; P. Vossough H. Haddad Deylami (Acta Medica Iranica, 2004)
Histiocytosis of Langerhans cells (class 1 histiocytosis) consists of a range of clinical manifestations, including bone eosinophilic granuloma, Hand-Schüller-Christian syndrome, and Letterer-Siwe disease. These syndromes represent a spectrum of severity and prognosis of an underlying disorder which is usually sporadic. This report describes three cases in one family, who developed the disease a few years after their brother was discovered to have histiocytosis. All three patients had the same clinical manifestations. They had hyperthermia, eczematic rash, swelling in skull, hand and foot. Radiological data included lytic areas in the skull and fourth metacarpal. Serology for Epstein-Barr infection was negative. Infiltration of abnormal Langerhans cell histiocytes was demonstrated upon bone biopsy. Chemotherapy was administered. One case (male) died after a year of chemotherapy. In another case (female) chemotherapy was unsuccessful, but T-cell suppressor (cyclosporin) induced remission. In the third case (female), chemotherapy was successful.